Investigating the Effect of Using Glyphosate on Microbial Soil in Sweet Corn Cultivation - Thi Hong Tho, Nguyen; Agustian, Agustian; Hermansah, Hermansah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Glyphosate affects the activity of certain soil microbial. Depending on the soil type and concentration, Glyphosate will have different effects. The study determined the effect of Glyphosate on the microbial population and the effect of its different volumes on ?-Glucosidase activity on Ultisol used in corn cultivation. The study used a completely randomized design (CRD), two factors with three replicates. The first factor was liming. The second element was Glyphosate at a dosage of 0, 5, 6, 7 L/ha. The study was conducted at the Department of Greenhouse Agriculture, Andalas University, from July to November 2022. The results showed that although there was no interaction and statistically significant between treatments for the total bacteria population. However, the treatment used lime and low volumes of Glyphosate gave the total bacteria population high density. ?-Glucosidase, an enzyme produced from a specific type of bacteria in soil, decreased activity while combining lime treatment and Glyphosate, especially from the dosage at 6 L/ha, and had a statistically significant interaction between lime factor and herbicide after the second spray (p<0.05). In conclusion, Glyphosate and lime can alter and reduce microbial soil activity and number, particularly at high 6 and 7 L/ha volumes.